The Western Necropolis of Cyrene: the Wadi Belghadir road. (2nd July 2019) - Di Valerio, Eugenio
Abstract: The Western Necropolis represents one of the most monumental and spectacular sections of the Cyrene cemeteries, with rock-cut monuments, still quite well preserved, along a funerary road. The earliest examples of monumental tombs in this context date to the second half of the sixth and the beginning of the fifth centuries BC, with tombs displaying rock-cut porticos in Doric, Aeolic or Ionic styles, and with the slightly later tombs having architectonic facades characterized by false 'contracted' porticos and overhanging lintels ending with two acroteria, mainly dating to the fifth century. The fourth century and the Hellenistic age, in this section of the necropolis, is attested by rock-cut chamber tombs, often with painted Doric friezes, and loculi. In Roman times, apart from a few examples of new tombs, most of the Roman funerary monuments reuse earlier tombs or are tombs that have been in constant use from previous periods. These phenomena of transformation and reuse of earlier monuments are quite well know for Cyrene, but are more evident from the middle and late imperial period; in later periods we even see the total re-functionalization of the monument. The monumental appearance of the Western Necropolis and its location in a quite remote area, are unfortunately the main reasons for the destruction of the tombs, which have been quite heavily looted: marble statues, busts and portraits have particularly suffered. Abstract : مقبرة قوريني الغربية : طريق وادي بالغدير يوجينيو دي فاليريو تمثل المقبرة الغربية من مقابر قوريني واحدة من أكثر أجزائها ضخامة و روعة، و ذلك بسبب معالمها المحفورة في الصخر و التي لا تزال محفوظة بشكل جيد على طول الطريق الجنائزي. يرجع تاريخ أقدم الأمثلة على القبور ذات النصب التذكارية (monumental tombs) في هذا السياق إلى النصف الثاني من القرن السادس وبداية القرن الخامس قبل الميلاد، بقبور ذات أروقة منقوشة على الصخر بالأسلوب الدوري أو الأيولي أو الأيوني، وفي القبور المتأخرة قليلاً تظهر الواجهات المعمارية التي تتميز بأروقة كاذبة متقلصة (contracted) وأعتاب متدلية (overhanging lintels) و التي تنتهي بزوج من الاكروتيريا ( acroteria )، و التي يرجع تاريخها في الأساس إلى القرن الخامس . و تشهد القبور المحفورة بالصخر في هذا الجزء من المقبرة على القرن الرابع والعصر الهلنستي و ذلك بأفاريزها الدوريه الملونة غالباً و المحاريب (loculi) التي توجد بها . و في العصر الروماني، و باستثناء بعض الأمثلة لقبور جديدة، فإن معظم المعالم الجنائزية الرومانية تعيد استخدام القبور القديمة أو القبور التي كانت تستخدم و بشكل دائم في الفترات السابقة . إن ظاهرة التحول وإعادة استخدام المعالم السابقة معروفة جيداً بقوريني، ولكنها أكثر وضوحاً في الفترة الإمبراطورية الوسطى والمتأخرة؛ نرى أيضاً في الفترات المتأخرة إعادة توظيف كاملة للمعلم . إن المظهر الضخم للمقبرة الغربية و وجودها في منطقة نائية تماماً هي الأسباب الرئيسية، و لسوء الحظ، لتعرض القبور بها للتدمير و النهب الشديد، حيث عانت و بشكل خاص التماثيل الرخامية والتماثيل النصفية واللوحات الفنية من هذا التدمير و النهب .